Glucocorticoids in preterm human milk - Muelbert, Mariana; Alexander, Tanith; Vickers, Mark H.; Harding, Jane E.; Galante, Laura; Bloomfield, Frank H.; , the DIAMOND study group; Muelbert, Mariana; Alexander, Tanith; Galante, Laura; Asadi, Sharin; Chong, Clara Y.L.; et al. (Frontiers in Nutrition, 2022)
Background Glucocorticoids (GCs), cortisol and cortisone, are essential regulators of many physiological responses, including immunity, stress and mammary gland function. GCs are present in human milk (HM), but whether maternal and infant factors are associated with HM GC concentration following preterm birth is unclear. Materials and methods HM samples were collected on postnatal day 5 and 10 and at 4 months’ corrected age (4m CA) in a cohort of moderate- and late-preterm infants. GCs in HM were measured by liquid chromatography-tandem mass spectrometry. Relationships between GCs in HM and both maternal and infant characteristics were investigated using Spearman’s correlations and linear mixed models. Results 170 mothers of 191 infants provided 354 HM samples. Cortisol concentrations in HM increased from postnatal day 5–4m CA (mean difference [MD] 0.6 ± 0.1 ng/ml, p < 0.001). Cortisone concentration did not change across lactation but was higher than cortisol throughout. Compared to no antenatal corticosteroid (ANS), a complete course of ANS was associated with lower GC concentrations in HM through to 4m CA (cortisol: MD –0.3 ± 0.1 ng/ml, p < 0.01; cortisone MD –1.8 ± 0.4 ng/ml, p < 0.001). At 4m CA, higher maternal perceived stress was negatively associated with GC concentrations in HM (cortisol adjusted beta-coefficient [aβ] –0.01 ± 0.01 ng/ml, p = 0.05; and cortisone aβ –0.1 ± 0.03 ng/ml, p = 0.01), whereas higher postpartum depression and maternal obesity were associated with lower cortisone concentrations (aβ –0.1 ± 0.04 ng/ml p < 0.05; MD [healthy versus obese] –0.1 ± 0.04 ng/ml p < 0.05, respectively). There was a weak positive correlation between GC concentrations in HM and gestational age at birth (r = 0.1, p < 0.05). Infant birth head circumference z-score was negatively associated with cortisol concentrations (aβ –0.01 ± 0.04 ng/ml, p < 0.05). At hospital discharge, fat-free mass showed a weak positive correlation with cortisol concentrations (r = 0.2, p = 0.03), while fat mass showed a weak negative correlation with cortisone concentrations (r = –0.25, p < 0.001). Conclusion The mammary gland appears to protect the infant from cortisol through inactivation into cortisone. Maternal and infant characteristics were associated with concentration of GCs in HM, including ANS, stress and depression scores, obesity, gestational age and infant size. The effects of HM glucocorticoids on long-term health outcomes requires further research.